Skala Kematangan Karier Siswa SMK - Krisphianti, Yuanita Dwi; Nurwulansari, Fenti Adelia (Universitas Nusantara PGRI Kediri, 2022)
The results of the preliminary study found that the career maturity of SMK students was low, including a) students did not have plans for continuing their careers after graduating from school, b) students did not have an effort to find information on the chosen career major, c) students were not interested in reading information about the chosen career, and students have difficulty deciding where to go and what to do when they graduate from school. Researchers need to strive to increase the career maturity of vocational students. To measure the increase in career maturity in this effort, the researcher developed an instrument in the form of a valid and reliable vocational maturity scale for vocational students. Therefore, this article describes the validity and reliability test of the career maturity scale of vocational students which has been developed by the researchers themselves. Based on the results of the validity test that was given to 139 students of class XI SMK Pemuda Papar, 55 valid scale items were obtained with a table of 0.166 and a reliable level of 0.892. Of the 55 valid items, all represent every indicator of career maturity. Based on the validity and reliability test of the instrument, the career maturity scale can be used to measure the career maturity level of the Pemuda Papar Vocational School students at the next research stage.